Keseimbangan Lansia Yang Tinggal di Komunitas - Anastasia Martha; Alida Nella Fedelina Rassa; Agung Kurniawan Saputra (Jurnal Ners, 2025)
Background: Aging is typically accompanied by physical and physiological decline, which causes people to act or refrain from engaging in a variety of activities, including those that are related to balance. Elderly people who have balance and coordination issues are more likely to fall. Objective To ascertain the proportion of senior citizens residing in the neighborhood. Method: An observational descriptive study was used for this investigation. Results of the Study: The average age of the 83 respondents was 66.86 years. According to the TUG Test, 90.36% of senior citizens are at little risk of falling. 91.57% of the elderly have a low risk of falling, according to the four square test; 83.13% of the elderly have normal balance, according to the FRT; and 54.22% of the elderly have normal balance, according to the FUKUDA. Conclusion : older people in metropolitan areas are well-balanced. This research highlights the value of a caring communal setting and easy access to medical resources in enhancing the well-being and equilibrium of senior citizens. Therefore, in order to build an age-friendly community and support the mobility and balance of the old, initiatives to improve their welfare must take a comprehensive approach that incorporates physical, social, and environmental components.